REPRESENTATION OF FEMINISM IN THE NOVEL RUMAH UNTUK ALIE BY LENN LIU: A SEMIOTIC STUDY - Wa Winta Batauga, Leni; Susiati, Susiati; Taufik, Taufik (LLDIKTI Wilayah X, 2025)
This study aims to describe the linguistic forms and types of feminism constructed in the novel Rumah untuk Alie by Lenn Liu and the meaning of signs that represent feminism in the novel Rumah untuk Alie by Lenn Liu. The data were analysed descriptively according to Roland Barthes' semiotic theory, which includes three layers of meaning: denotative, connotative, and myth.The results show that the linguistic forms in the novel Rumah Untuk Alie are dominated by declarative and imperative sentences used by the main character to voice disappointment, anger, and resistance to gender injustice. The types of feminism represented include radical feminism, especially cultural radical and existentialist, and liberal feminism. Meanwhile, the signs in Lenn Liu's Rumah Untuk Alie, both verbal and symbolic, reveal social myths that place women as subordinate parties.